The Central Role of the Family in Educating and Shaping Children's Honesty - Sianipar, Rustida; Herman, Samuel (Asian Journal of Applied Education (AJAE), 2024)
This study examines the role of the family in shaping children's honesty through moral education full of compassion. The method used is a literature review, which involves literature analysis related to the role of the family in moral education and character development of children. The results of the study show that families that create a warm and supportive environment have a significant impact on the formation of children's character. Honesty instilled by parents through daily examples and examples has been proven to have a long-term positive effect. Children who grow up in a supportive environment and get direct examples from parents regarding the values of honesty tend to be honest and trustworthy individuals. The conclusion of this study emphasizes the importance of the role of the family in educating children's honesty. Parents' consistency in showing honesty in daily life is effective in shaping the character of children who are moral and reliable in the future.